Local institutional investors and corporate monitoring: Evidence from cross-listed Korean stocks in the US market - CHOI, Changhwan (Institutional Knowledge at Singapore Management University, 2024)
Using Korean firms that are cross-listed in the US market, this paper investigates whether there are standalone effects of geographic and market proximity of institutional investors on monitoring performance. We find that Korean institutional ownership is negatively associated with earnings management while the US institutional ownership has no impact on earnings management. This suggests that there is the geographic proximity advantage over the market proximity advantage in the emerging markets. Furthermore, we also show that the impact of geographic proximity is stronger for firms with high informational opacity